Aurally Aided Visual Search in Three-Dimensional Space. - Bolia, Robert S. (Human Factors: The Journal of the Human Factors and Ergonomics Society)
We conducted an experiment to evaluate the effectiveness of spatial audio displays on target acquisition performance. Participants performed a visual search task with and without the aid of a spatial audio display. Potential target locations ranged between plus and minus 180 degrees in azimuth and from -70 degrees to +90 degrees in elevation. Independent variables included the number of visual distractors present (1,5, 10, 25, 50) and the spatial audio condition (no spatial audio, free-field spatial audio, virtual spatial audio). Results indicated that both free field and virtual audio cues engendered a significant decrease in search times. Potential applications of this research include the design of spatial audio displays of aircraft cockpits and ground combat vehicles.